3.1 Etica di impresa - Ciappei, Cristiano (Firenze University Press, 2006)
This book proposes theoretical reflections, tools and techniques for a business ethic that aims at the construction of social welfare. A correct connotation of business ethics is seen in its role of interface between the ontology of the "enterprise phenomenon" and the social ethics of its operation. The book upholds the theory that business development can be such only if it leads to the emancipation of the persons affected by the same. A development in which, that is, it is not only the economic results that have bearing, but above all the way in which they are obtained and exploited. In enterprise, too, priority should hence be given to a practice implemented in a conscientious manner which enhances the complete development of the persons involved, whether they are workers or consumers.